Implementasi Sistem Usability Scale dalam Evaluasi Usability Tiktok - Silvia; Rahayu Amalia (JSAI (Journal Scientific and Applied Informatics), 2025)
The development of information technology has brought significant changes to how humans interact, one of which is through social media. TikTok has become one of the popular social media applications with various attractive features that support users' creativity and self-expression. This study aims to evaluate the usability level of the TikTok application using the System Usability Scale (SUS) method. This method assesses user experience based on 10 statements rated on a Likert scale ranging from "strongly disagree" to "strongly agree." Data were collected through questionnaires distributed in online. The analysis results showed an average SUS score of 73.4, indicating that TikTok has a good and acceptable usability level. This study provides insights into TikTok's strengths and weaknesses in meeting user needs and offers recommendations for further development.